Synthesis by solution combustion and optical characterization of violet NASICON-type Mg0.45Co0.05Ti2(PO4)3 pigment. (October 2018) - Chavarriaga, E.A.; Lopera, A.A.; Wermuth, T.B.; Restrepo, O.J.; Bergmann, C.P.
Abstract: In this paper, Mg0.5 Ti2 (PO4 )3 with the NASICON-type structure was evaluated for the first time as a possible host structure of Co 2+ for obtaining an inorganic pigment with violet color. The powders were synthesized by solution combustion synthesis using glycine (G) and urea (U) as fuels and different oxidizer-to-fuel (O/F) ratios when ammonium nitrate was used as an extra-oxidant. However, X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) technics showed that the as-prepared powders were amorphous, which is due possibly by the effect of fire retardant of the diammonium hydrogen phosphate used as a source of phosphate during the synthesis. The calcination temperature for the as-prepared powders was established using Differential scanning calorimetry and Thermogravimetry (DSC/TGA), which showed crystallization temperatures less than 900 °C. Therefore, the powders were calcined at 900 °C for 3 h and the formation of the NASICON structure was confirmed using XRD and FTIR. The morphology was evaluated using Scanning electron microscopy (SEM) and the micrographs shown aggregated particles with irregular shapes. The optical properties of the inorganic pigments were studied using diffuse reflectance ultraviolet-visible-near infrared (Uv–Vis–NIR) spectroscopy, which showed that the band gap of the samples was E g, indirect = 3.13 eV for NASICON Mg0.5 Ti2 (PO4 )3 and E g, indirect = 3.17 eV for NASICON Mg0.45 Co0.05 Ti2 (PO4 )3 . For this reason, the band gap of the system does not depend on dopping with Co 2+ for the concentration used. Thus, the mechanism of color is due to electronic transitions in DMSO-d6 orbitals with octahedral coordination for Co 2+ in NASICON Mg0.45 Co0.05 Ti2 (PO4 )3 . TSR (total solar reflectance) between 700 nm and 1800 nm were 95.94% for NASICON Mg0.5 Ti2 (PO4 )3 and 81.41% for NASICON Mg0.45 Co0.05 Ti2 (PO4 )3 . These results show that the pigments could be potential candidates for the application as cold pigments. Graphical abstract: Highlights: Violet NASICON-type Mg0.45 Co0.05 Ti2 (PO4 )3 was prepared by solution combustion. The influence of Oxidizer to Fuel ratio upon Mg0.45 Co0.05 Ti2 (PO4 )3 pigment formation was studied. Total solar reflectance NIR of NASICON Mg0.45 Co0.05 Ti2 (PO4 )3 was TSR = 81.41%. The band gap of NASICON Mg0.45 Co0.05 Ti2 (PO4 )3 was Eg, indirect = 3.17 eV.